Gaseous Air Quality Indicators along Traffic Routes in Greater Freetown, Sierra Leone - Taylor, Eldred Tunde; Jalloh, Alie Dukuray; Jallow, Haddijatou (International Journal of Geography and Geology, 2016)
Urban air pollution is increasingly getting attention in developing countries in recent years. It was against this backdrop that this piece of work examined three indices of air pollution along a single carriage road (Kissy Road) and dual carriage road (Wilkinson Road) on either direction. Brief monitoring spell of nitrogen dioxide (NO2); sulphur dioxide (SO2) and carbon monoxide (CO) were made between August 2015 and September 2015 using the Drager X am 5000 realtime monitor for the different gases. Diurnal monitoring was made in the morning, afternoon and evening periods representing peak and off peak periods. Results indicated higher levels of pollution at Kissy Road relative to Wilkinson Road. Considerable variation were also observed among the pollutants for the two sites and the hourly average values revealed levels that are within ambient air quality standards except for SO2. Field observations revealed poorly maintained vehicles, human behavioral pattern, frequent traffic jams were attributed to the observed values.